Neurofilament protein in cerebrospinal fluid: a potential marker of activity in multiple sclerosis. Issue 3 (1st March 1998) - Lycke, J N; Karlsson, J-E; Andersen, O; Rosengren, L E
Abstract : The neurofilament protein is a major structural protein of neurons and a marker for axonal damage. The concentrations of the light subunit of the neurofilament triplet protein (NFL) in CSF were significantly increased in patients with relapsing-remitting multiple sclerosis compared with healthy controls (p<0.001). Seventy eight per cent of patients with multiple sclerosis showed increased NFL concentrations. Significant correlations between the NFL concentration in CSF and clinical indices were discerned for disability, exacerbation rate, and time from the start of the previous exacerbation to the time of the lumbar puncture. The results suggest that axonal damage occurs during relapsing-remitting multiple sclerosis and that the damage contributes to disability and the appearance of clinical exacerbations. The concentration of NFL in CSF is a potential marker of disease activity in multiple sclerosis and might be useful in future clinical trials of multiple sclerosis.